Optimization of Turbine Blade Pitch Angle of a Home-built Wind Turbine for Maximum Power Output - Mugo, Sammy; H. Masinde, Barasa; T. Cherop, Peter (Journal of Renewable Energy and Mechanics, 2024)
Wind energy greatly reduces the world’s dependence on fossil fuels (oil and natural gas), and is environmentally friendly. One of the most cost-effective alternatives of energy sources is wind power. This study used a horizontal axis wind turbine to investigate the optimal blade pitch angle that can give maximum electrical output. A proportional integral derivative pitch controller was used to establish blade pitch angles. Wind speeds of 3, 4, 5 and 6 m/s were run at every pitch angle respectively, and a maximum electrical power output was 1124.7W at a blade pitch angle of 16.80 when a wind speed of 6 m/s was used. Every wind speed was run for 100 seconds. A simulation, using Visual Basic 6 software, was done at the respective blade pitch angles, and a wind speed of 6 m/s. The electricity produced was recorded. The simulated electrical power produced yielded a relationship that predicted the electrical power output with a coefficient of determination (R2) of 0.9752; this shows a very close agreement with actual electric output values.